Burnout syndrome and job performance in health personnel (Revista Innova Educación, 2020)
Health professionals are the most vulnerable to factors that trigger work stress associated with Burnout syndrome, which usually affects their work performance and the quality of their attention, causing frequent complaints from users, particularly at the first level of attention at health system centers. Objective: To identify the presence of the Burnout syndrome in its 3 dimensions: emotional exhaustion, depersonalization, personal fulfillment to identify the level of work performance in its four scales: technical quality and medical attention, training and continuing education, productivity, skills; and to establish whether there is a relation between Burnout syndrome and work performance in health personnel at the Vallecito I-3 Health Center, Puno (Peru). Method: Descriptive-correlational, the sample consisted of the total number of workers in the health establishment. The instruments were the Maslach Burnout Inventory test and the job performance self-assessment questionnaire. Results: Burnout Syndrome 7.09 on a scale of 1 to 10 (s = 2.32), work performance 35.71 on a scale of 0 to 40 (s = 0.81), there is no correlation between both variables (r = 0.063). Conclusion: It is concluded that the Burnout syndrome reaches medium level, the work performance is high and there is no relationship established between the Burnout syndrome and the work performance of health personnel.
Keywords: Burnout síndrome; health personnel; job performance; primary care